Long-term melatonin treatment reduces ovarian mass and enhances tissue antioxidant defenses during ovulation in the rat - Chuffa, L. G. A. [UNESP]; Amorim, J. P. A. [UNESP]; Teixeira, G. R. [UNESP]; Mendes, L. O. [UNESP]; Fioruci, B. A. [UNESP]; Pinheiro, P. F. F. [UNESP]; Seiva, F. R. F. [UNESP]; Novelli, E. L. B. [UNESP]; Mello Júnior, Wílson de [UNESP]; Martinez, M.; Martinez, Francisco Eduardo [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2011)
Melatonin regulates the reproductive cycle, energy metabolism and may also act as a potential antioxidant indoleamine. The present study was undertaken to investigate whether long-term melatonin treatment can induce reproductive alterations and if it can protect ovarian tissue against lipid peroxidation during ovulation. Twenty-four adult female Wistar rats, 60 days old (± 250-260 g), were randomly divided into two equal groups. The control group received 0.3 mL 0.9% NaCl + 0.04 mL 95% ethanol as vehicle, and the melatonin-treated group received vehicle + melatonin (100 µg·100 g body weight-1·day-1) both intraperitoneally daily for 60 days. All animals were killed by decapitation during the morning estrus at 4:00 am. Body weight gain and body mass index were reduced by melatonin after 10 days of treatment (P < 0.05). Also, a marked loss of appetite was observed with a fall in food intake, energy intake (melatonin 51.41 ± 1.28 vs control 57.35 ± 1.34 kcal/day) and glucose levels (melatonin 80.3 ± 4.49 vs control 103.5 ± 5.47 mg/dL) towards the end of treatment. Melatonin itself and changes in energy balance promoted reductions in ovarian mass (20.2%) and estrous cycle remained extensive (26.7%), arresting at diestrus. Regarding the oxidative profile, lipid hydroperoxide levels decreased after melatonin treatment (6.9%) and total antioxidant substances were enhanced within the ovaries (23.9%). Additionally, melatonin increased superoxide dismutase (21.3%), catalase (23.6%) and glutathione-reductase (14.8%) activities and the reducing power (10.2% GSH/GSSG ratio). We suggest that melatonin alters ovarian mass and estrous cyclicity and protects the ovaries by increasing superoxide dismutase, catalase and glutathione-reductase activities.
Keywords: Melatonin; Ovary mass; Lipid peroxidation; Antioxidant defenses; Superoxide dismutase